Regulating Network Industries beyond Economic Theories: An Analysis of IP Interconnection Policies to Support Voice Services in the EU from the perspective of Public Interest Theories (Law, State and Telecommunications Review, 2017)
Purpose ”“ The study aims to analyze the extent to which economic theories of network industries could anticipate the behavior of regulators regarding the promotion of network access and interconnection policies in telecommunication markets.Methodology/approach/design ”“ The paper first analyzes the main economic arguments for regulating network industries, in order to highlight the regulatory metalinguistics they contain. Then, the study indicates some critiques to economic rationality addressed by Public Interest Theories of Regulation. At last, it verifies how well economic theories of network industries explain IP interconnection policies recently developed in two European countries, namely, France and Germany.Findings ”“ European regulator's decisions of imposing IP interconnection obligations on fixed network operators suggest that regulatory intervention on such fields is strongly influenced by non-economic values, such as effective competition and technological neutrality.